Peningkatan Kemampuan Mengenal Huruf Melalui Media Tutup Botol di PAUD Nusa Indah Kota Sawahlunto - Yusri Mudarlis; Asdi Wirman (Khirani: Jurnal Pendidikan Anak Usia Dini, 2025)
This research was motivated by the low ability to recognize letters in PAUD Nusa Indah, Sawahlunto City. This low ability is caused by a lack of stimulation appropriate to the child's developmental stages, and the media used by educators is less varied, so that children are less interested in learning, especially recognizing letters. This research aims to see children's ability to recognize letters, namely 1) Mentioning vowel sounds a, i, u 2) Mentioning letter sounds that are similar to b, d.p 3) Connecting letters into syllables 4) Connecting syllables into meaningful words 5) Adding vowel letters in meaningful words 6) Add up the consonant letters in meaningful words.This research uses a classroom action approach. The research subjects were 10 PAUD children in Nusa Indah, Sawahlunto City. The research instrument used was an observation and documentation format, and after going through the planning, implementation, observation and reflection stages, the data obtained was analyzed using percentages.Based on the results of the analysis, it can be concluded that, there is an increase in the ability to recognize letters through bottle cap media. It is recommended that PAUD educators and parents can optimize the development of children's ability to recognize letters in accordance with the stages of early childhood development through the use of game media, including bottle cap media.